F08 The functional rating taskforce for pre-huntington's disease: results so far. (16th November 2010) - Evans, K; Anderson, K; Borowsky, B; Giuliano, J; Guttman, M; Ho, A; Paulsen, J; Sills, T; Vaccarino, A; van Kammen, D; ,
Abstract : Background: The earliest clinical manifestations of Huntington's (HD) disease are poorly characterized, and there is a need for clinical scales designed specifically to measure early signs and symptoms in individuals with the huntingtin gene mutation. Aims: The Functional Rating Scale Taskforce for pre-Huntington's Disease (FuRST-pHD) is comprised of a multidisciplinary team of clinical experts, drug developers, and psychometricians that work in close association with advocacy groups and HD gene carriers to develop a valid functional rating scale to assess changes in symptom severity in pre- and early-HD. Such a measurement tool is essential in order to assess the efficacy of early intervention treatments. Methods: FuRST-pHD has established a data-driven, iterative, and collaborative process to develop a clinical scale to assess symptoms and their functional impact in pre- and early-HD. The process involves input from numerous sources to identify relevant symptom domains, including gene expansion carriers, caregivers, and experts from a variety of fields, as well as knowledge gained from the analysis of data from ongoing observational studies in HD (PREDICT-HD and REGISTRY) using existing clinical scales. Clinical scale interview questions were developed by expert teams of clinicians and psychometricians in order to gather data about the identified symptom domains through field testing in pre-HD individuals. We report here the progress of the FuRST-pHD initiative. Results: At present, more than 60 structured interview questions aimed at determining the presence and extent of severity in a number of symptom domains have been developed, including motor, cognitive and psychiatric symptoms. The interview questions have undergone, or are undergoing, testing at various clinical centres involved with FuRST-pHD and PREDICT-HD. We present data supporting the development of items to assess a number of symptoms in pre-HD, including Anger and Irritability, Obsessions and Compulsions, and Depression and Anxiety. Conclusions: Many CAG expanded individuals clearly exhibit a range of motor, cognitive and psychiatric signs years prior to clinical diagnosis. The present data suggest a number of behavioural/psychiatric symptom clusters that should be assessed in order to capture fully the scope of dysfunction in pre-HD individuals.